A case of acute suppurative arthritis of the temporomandibular joint - NEGISHI, Akihide; MOGI, Kenji; TAKANO, Atsushi; NAKASONE, Yoshiki; KAMEI, Keiko (Japanese Journal of Oral and Maxillofacial Surgery, 2003)
A rare case of suppurative arthritis of the temporomandibular joint (TMJ) is reported. A 47-year-old man was referred to our hospital because of diffuse swelling and pain in the right TMJ and malocclusion caused by a left shift of the mandible. The patient had been treated for periodontitis at a dental clinic during the previous 2 months. The swelling and pain increased after extraction of the right upper third molar. A radiograph revealed anterior deviation of the right condyle. The anterior region of the right TMJ showed a low density area on computed tomographic examination. After administration of antibiotics (ABPC+CLDM), lavage of the right TMJ cavity was performed. The results of microbiological examination were negative, and there was no evidence of ankylosis or other disorders of TMJ. The symptoms subsequently resolved. We suspected that the inflammation associated with the upper third molar affected the TMJ and caused the symptoms in this patient.